RELIGIOUS SYNCRETISM IN THE NAZAR TRADITION AT THE SACRED TOMB OF TUKJI, NAGARI SIALANG GAUNG, DHARMASRAYA, WEST SUMATRA - Tommy Hardi Putra; Novi Hendri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Religious syncretism in Minangkabau is normatively framed within the philosophy of Adat Basandi Syarak, Syarak Basandi Kitabullah (ABS-SBK). This study examines the nazar (vow) tradition at the Tukji Sacred Tomb, Nagari Sialang Gaung, Dharmasraya, which remains academically unexplored. The central problem revolves around a fundamental theological tension: on one hand, traditionalist adat leaders and ulama legitimize the practice as a legitimate cultural heritage in accordance with syarak due to its function in preserving social cohesion and communal identity. On the other hand, puritan groups consider it a deviation from monotheism, bid'ah, and potentially shirk. This tension is compounded by the absence of scholarly inquiry that deeply captures the dynamics of meaning negotiation among stakeholders ninik mamak, ulama, tomb custodians, and pilgrims amid contemporary currents of religious purification. This research aims to: (1) describe the structure and symbolic meanings of the nazar tradition; (2) uncover the mechanisms of meaningful negotiation among stakeholders; and (3) analyze the theological and social implications of sustaining this syncretic tradition. Using a qualitative ethnographic approach, data were collected through observation, semi-structured in-depth interviews with ten purposively selected key informants, and visual documentation. Findings reveal five interrelated forms of syncretism: structural, ritual, symbolic, ideological, and socio-cultural. Analysis reveals that syncretism operates as an adaptive strategy termed maslahah adaptive efforts by the community to preserve the essence of the tradition while adjusting controversial ritual elements in response to theological critiques. This research confirms that the nazar tradition is not passive cultural preservation, but rather an arena of active negotiation between Islamic teachings and local wisdom, serving to strengthen solidarity and communal identity amid changing religious discourse.